High-alkali-resistance in-situ crosslinking anion exchange polymer, membrane and device
By introducing high alkali-resistant cationic groups and in-situ polymerization side chain structure into the polymer backbone of the anion exchange membrane, the chemical and dimensional stability of the existing membranes are solved, and the comprehensive optimization of membrane performance and long-term stable operation are achieved.
Patent Information
- Application Number
- CN202411693696.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
AI Technical Summary
While improving ion conductivity, existing anion exchange membranes often sacrifice chemical stability and dimensional stability, making it difficult to meet the application requirements under long-term and high-load operating conditions.
By introducing high alkali resistance cationic groups and in-situ polymerizable side chain structures into the polymer framework structure, a high alkali resistance in-situ crosslinked anion exchange polymer is formed, thereby improving the alkali resistance stability, mechanical strength and dimensional stability of the film.
It has achieved comprehensive optimization of the performance of anion exchange membrane, maintained high ion conductivity and significantly improved alkali resistance stability and dimensional stability. It is suitable for various electrochemical applications such as alkaline electrolytic water and fuel cells.
Smart Images

Figure CN119529244A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular to a highly alkali-resistant in-situ cross-linked anion exchange polymer, a membrane and a device. Background Art
[0002] Anion exchange membranes, as a key functional membrane material, play an important role in electrochemical devices such as water electrolysis to produce hydrogen, alkaline fuel cells, flow batteries and electrodialyzers because of their ability to selectively conduct anions. These application scenarios require anion exchange membranes to have high ion conductivity, excellent chemical stability, good mechanical strength and outstanding dimensional stability. However, the anion exchange membranes currently on the market often have shortcomings in comprehensive performance and are difficult to meet the stringent requirements in practical applications.
[0003] Ion conductivity is one of the important indicators for measuring the performance of anion exchange membranes, and is directly related to the energy conversion efficiency of electrochemical devices. However, high ion conductivity is often in conflict with chemical stability. Traditional anion exchange membranes often sacrifice chemical stability while improving ion conductivity, especially in alkaline environments, where membrane materials are prone to degradation, resulting in a rapid decline in performance. This contradiction limits the application of anion exchange membranes under long-term, high-load operating conditions.
[0004] In addition to chemical stability, dimensional stability is crucial to ensuring the performance and operational stability of electrochemical devices. However, many existing anion exchange membranes are prone to deformation or damage when used for a long time or under extreme conditions, resulting in device performance degradation or even failure.
[0005] Patent CN 111040137 A proposes an innovative anion exchange polymer and its preparation method, the main chain of which contains biphenyl, terphenyl and piperidine quaternary ammonium cation structural units. This design not only improves the chemical stability of the membrane material, but also gives it excellent ionic conductivity, mechanical strength and anti-swelling properties. However, although this technology has made significant progress in many aspects, it still has shortcomings in alkaline stability and dimensional stability. Especially when running for a long time or in a highly alkaline environment, the performance of the membrane material is prone to decline, resulting in a shortened operating cycle of the electrolyzer.
[0006] In summary, the anion exchange membranes in the prior art have many deficiencies in ion conductivity, chemical stability and dimensional stability, and are difficult to meet the high requirements in practical applications. Therefore, the development of a new anion exchange membrane material that can maintain high ion conductivity and significantly improve chemical stability and dimensional stability has become an urgent need in current research. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the present invention provides a highly alkali-resistant in-situ cross-linked anion exchange polymer, membrane and device. By introducing highly alkali-resistant cationic groups and side chain structures that can be in-situ polymerized during the film casting process into the polymer skeleton structure, the alkali resistance stability, mechanical strength and dimensional stability are improved while maintaining the high ion conductivity of the anion exchange membrane, thereby achieving comprehensive optimization of the anion exchange membrane performance to meet the high requirements of actual battery stack assembly and long-term operation.
[0008] To achieve the above object, the present invention provides the following technical solution: a highly alkali-resistant in-situ cross-linked anion exchange polymer, wherein the anion exchange polymer adopts a polyaryl skeleton structure, and introduces a highly alkali-resistant cationic group and an in-situ polymerized side chain structure into the polyaryl skeleton structure, and the general structural formula is as follows:
[0009] Wherein, A is an aromatic group, and X has a value of 50-99.
[0010] Furthermore, the aryl group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene.
[0011] The present invention provides a method for preparing a highly alkali-resistant in-situ cross-linked anion exchange polymer, the specific steps of which are as follows: 100 parts of an aromatic compound and 100 parts of quinuclidinone hydrochloride or 3-quinuclidinone are mixed in a solvent, reacted with Lewis acid at 0°C, impurities are removed, and dried to obtain an intermediate polymer; 100 parts of the intermediate polymer, 1-50 parts of p-chloromethylstyrene and 100-1000 parts of methyl iodide are mixed, reacted under alkaline conditions, filtered, washed and dried to obtain an anion exchange polymer.
[0012] Furthermore, the general structural formula of the anion exchange polymer is as follows:
[0013] Wherein, A is an aromatic group, and X has a value of 50-99.
[0014] Furthermore, the aryl group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene.
[0015] The present invention provides a highly alkali-resistant in-situ cross-linked anion exchange membrane, which is prepared by using a highly alkali-resistant in-situ cross-linked anion exchange polymer. The structural formula of the highly alkali-resistant in-situ cross-linked anion exchange polymer is as follows:
[0016] Wherein, A is an aromatic group, and X has a value of 50-99.
[0017] Furthermore, the highly alkali-resistant in-situ cross-linked anion exchange polymer is prepared by the following method: 100 parts of an aromatic compound and 100 parts of quinuclidinone hydrochloride or 3-quinuclidinone are mixed in a solvent, reacted with Lewis acid at 0°C, impurities are removed, and dried to obtain an intermediate polymer; 100 parts of the intermediate polymer, 1-50 parts of p-chloromethylstyrene and 100-1000 parts of methyl iodide are mixed, reacted under alkaline conditions, filtered, washed and dried to obtain an anion exchange polymer.
[0018] The present invention also provides a method for preparing the above-mentioned highly alkali-resistant in-situ cross-linked anion exchange membrane, wherein a highly alkali-resistant in-situ cross-linked anion exchange polymer solution with a mass fraction of 1% to 50% is poured into a template and dried to obtain an anion exchange membrane.
[0019] Furthermore, the drying is performed at 50°C to 120°C for 30 minutes to 12 hours.
[0020] The present invention also provides a water electrolysis reactor, comprising the above-mentioned highly alkali-resistant in-situ cross-linked anion exchange membrane.
[0021] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention provides a highly alkali-resistant in-situ cross-linked anion exchange polymer, the core of which is the introduction of highly alkali-resistant cationic groups into the polymer skeleton structure and a side chain structure that can be polymerized in situ during the film casting process. This unique design not only maintains the high ion conductivity of the anion exchange membrane, but also significantly improves its alkali resistance stability, mechanical strength and dimensional stability, thereby achieving comprehensive optimization of membrane performance.
[0022] Furthermore, the present invention adopts a polyaryl skeleton, such as biphenyl, p-terphenyl, m-terphenyl, diphenylethane, 9,9-dimethylfluorene, etc. These aromatic groups give the polymer good thermal stability and chemical stability. Highly alkali-resistant cationic groups, such as quinuclidine derivatives, are introduced. These groups can remain stable in an alkaline environment and are not easily degraded, thereby extending the service life of the membrane. Side chain structures containing reaction sites for in-situ polymerization during the film casting process, such as chloromethylstyrene, are introduced. These sites form a cross-linked structure through in-situ polymerization, thereby enhancing the dimensional stability and mechanical strength of the membrane.
[0023] The anion exchange membrane prepared by the above-mentioned highly alkali-resistant in-situ cross-linked anion exchange polymer can maintain efficient ion conduction performance thanks to the highly alkali-resistant cationic groups in the polymer skeleton; the highly alkali-resistant cationic groups and the cross-linked structure jointly improve the alkali resistance of the membrane, enabling it to operate stably for a long time in an alkaline environment. The in-situ polymerized side chain structure enhances the cross-linking degree of the membrane and effectively prevents the dimensional change of the membrane during long-term use. Therefore, the membrane not only maintains high ion conductivity, but also significantly improves alkali resistance stability and dimensional stability, and is suitable for various electrochemical applications such as alkaline water electrolysis and fuel cells.
[0024] The highly alkali-resistant in-situ cross-linked anion exchange membrane of the present invention is applied in a water electrolysis reactor. The high ion conductivity ensures efficient ion transmission during the water electrolysis process and improves the electrolysis efficiency. The alkali resistance stability and dimensional stability ensure the long-term stable operation of the membrane in an alkaline environment and extend the service life of the equipment. Due to the excellent performance of the membrane, the frequency of replacement and maintenance is reduced, and the maintenance cost of the equipment is reduced.
[0025] In summary, the highly alkali-resistant in-situ cross-linked anion exchange polymer and membrane of the present invention have broad application prospects in the field of electrochemistry, and can provide efficient, stable and economical solutions for electrochemical applications such as water electrolysis and fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The ionic conductivity data of the anion exchange membrane of the present invention at 80°C; Figure 2 Data graph of ion conductivity retention rate of anion exchange membrane of the present invention after alkali immersion for 2000 hours. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0029] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0030] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0031] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0032] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" represents that all real numbers between "6-22" are listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0033] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0034] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0035] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0036] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0037] The present invention provides an anion exchange polymer, which adopts a polyaryl skeleton structure, and introduces a highly alkali-resistant cationic group and a side chain structure providing a reaction site for in-situ polymerization into the polyaryl skeleton structure. The general structural formula is as follows:
[0038] The aromatic group may be one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene; and the value of X is 50-99.
[0039] The preparation method of the anion exchange polymer is as follows: (1) 100 parts of an aromatic compound and 100 parts of quinuclidinone hydrochloride or 3-quinuclidinone are mixed in a solvent, reacted under the condition of 0°C with Lewis acid catalyst, impurities are removed, and dried to obtain an intermediate polymer; (2) 100 parts of the intermediate polymer, 1 to 50 parts of p-chloromethylstyrene and 100 to 1000 parts of methyl iodide are mixed, reacted under alkaline conditions, filtered, washed and dried to obtain an anion exchange polymer, wherein the anion exchange polymer is an anion of I - of functionalized polymers.
[0040] The anion exchange polymer is used for film casting to obtain anion exchange membrane having excellent ion conductivity, alkali resistance stability and dimensional stability, thereby achieving comprehensive optimization of the anion exchange membrane performance. The specific preparation steps are as follows: The anion exchange polymer is dissolved in a solvent to prepare a solution with a mass fraction of 1% to 50%, the anion exchange polymer solution is poured into the template, and dried at 50° C. to 120° C. for 30 min to 12 h to obtain an anion exchange membrane; Specifically, the anion exchange polymer solution in the template is polymerized in situ during the drying process to obtain a cross-linked network structure, namely, an anion exchange membrane. The obtained anion exchange membrane is immersed in different ion solutions to replace the anions on the anion exchange membrane with the required anions.
[0041] The present invention introduces highly alkali-resistant cationic groups into the polymer backbone structure and simultaneously introduces a side chain structure that can be polymerized in situ during the film casting process. The side chain structure provides a reaction site for in situ polymerization, thereby improving the dimensional stability of the membrane. The present invention improves the alkali resistance stability and dimensional stability while maintaining the high ion conductivity of the anion exchange membrane.
[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0043] Example 1 A is p-terphenyl, x=80 A method for preparing an in-situ cross-linked anion exchange membrane with high alkali resistance, the specific steps are as follows: (1) Weigh 10.0 mmol of p-terphenyl into a 100 mL three-necked flask, add 10.0 mmol of 3-quinuclidine hydrochloride, and add 10 mL of dichloromethane to dissolve the reactants. Add 12 mL of trifluoromethanesulfonic acid and 1 mL of trifluoroacetic acid at 0 °C, and stir mechanically for 12 hours. Pour the viscous purple product into 1M K2CO3 solution, soak at room temperature for 24 hours, filter to obtain a white solid product, wash it thoroughly with deionized water, and dry it to obtain an intermediate polymer with the following structural formula:
[0044] (2) Weigh 1.2 g of the intermediate polymer in a 100 mL single-necked flask, add 15 mL of dimethyl sulfoxide, and add 150 μL of trifluoroacetic acid to promote the dissolution of the polymer. After the polymer is completely dissolved, add 0.36 g of potassium carbonate and 0.05 g of p-chloromethylstyrene, and react at room temperature for 24 h. Then add 300 μL of iodomethane and react at room temperature for 48 h. Pour the reaction product into ethyl acetate to precipitate a yellow precipitate, wash it with ethyl acetate several times, then wash it with water and dry it, and obtain an anion of I - The functionalized polymer has the following structural formula:
[0045] (4) Weigh 1g of the functionalized polymer, add 50mL of dimethyl sulfoxide, and pour it into the groove of a flat glass plate after it is fully dissolved. Dry it at 80°C for 48 hours to form a film, and at the same time, form a cross-linked network structure in situ. After the film is peeled off the glass plate, it is immersed in a 1M KOH solution and ion exchange is performed at room temperature for 48 hours to obtain an anion of OH - The anion exchange membrane has the following structural formula:
[0046] Measurement of OH in pure water by four-electrode electrochemical impedance spectroscopy - Ionic conductivity. Figure 1 As shown, the ionic conductivity of the anion exchange membrane obtained in this embodiment is 180 mS / cm at 80°C; Figure 2 As shown in the figure, the ion conductivity retention rate of the anion exchange membrane obtained in this embodiment after alkali immersion for 2000 hours is 97.1%. The cross-linked structure significantly improves the alkali resistance stability of the anion exchange membrane.
[0047] Example 2 A is p-terphenyl, x=50 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows:
[0048] Example 3 A is p-terphenyl, x=99 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows:
[0049] Example 4 A is biphenyl, x=80 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows:
[0050] Measurement of OH in pure water by four-electrode electrochemical impedance spectroscopy- Ionic conductivity. Figure 1 As shown, the ionic conductivity of the anion exchange membrane obtained in this embodiment is 184 mS / cm at 80°C; Figure 2 As shown in the figure, the ion conductivity retention rate of the anion exchange membrane obtained in this embodiment after alkali immersion for 2000 hours is 96.8%. The cross-linked structure significantly improves the alkali resistance stability of the anion exchange membrane.
[0051] Example 5 A is 80% p-terphenyl + 20% m-terphenyl, x=80 Based on the preparation in Example 1, an anion exchange membrane was obtained, and the structural formula is as follows:
[0052] Example 6 A is 80% p-terphenyl + 20% diphenylethane, x=80 Based on the preparation of Example 1, the cationic group uses 3-quinuclidinone to obtain an anion exchange membrane with the following structural formula:
[0053] Example 7 A is 90% p-terphenyl + 10% dimethylfluorene, x = 80 Based on the preparation of Example 1, the cationic group uses 3-quinuclidinone to obtain an anion exchange membrane with the following structural formula:
[0054] Comparative Example 1 A is p-terphenyl, x=100 Based on Example 1, p-chloromethylstyrene was not added during the reaction, and step (2) was modified as follows: 1.2 g of the intermediate polymer was weighed into a 100 mL single-necked flask, 15 mL of dimethyl sulfoxide was added, and 150 μL of trifluoroacetic acid was added to promote the dissolution of the polymer. After the polymer was completely dissolved, 0.36 g of potassium carbonate and 300 μL of iodomethane were added, and the reaction was carried out at room temperature for 48 h. The reaction product was poured into ethyl acetate to precipitate a yellow precipitate, which was washed with ethyl acetate several times and then washed with water and dried to obtain an anion exchange membrane with the following structural formula:
[0055] The OH- ion conductivity of the fully wet anion exchange membrane in pure water was measured using the four-electrode AC impedance method. Figure 1 As shown, the ionic conductivity of the anion exchange membrane obtained in this embodiment is 142 mS / cm at 80°C; Figure 2 As shown in FIG. 1 , the ion conductivity retention rate of the anion exchange membrane obtained in this embodiment after 2000 hours of alkaline leaching is 94.9%. Compared with Example 1, the ion conductivity of Comparative Example 1 (see Figure 1 ) and alkali stability (see Figure 2) were significantly reduced, indicating that the cross-linked structure significantly improved the alkali stability of the anion exchange membrane.
Claims
1. A highly alkali-resistant in-situ cross-linked anion exchange polymer, characterized in that: The anion exchange polymer adopts a polyaryl skeleton structure, and introduces a highly alkali-resistant cationic group and an in-situ polymerized side chain structure into the polyaryl skeleton structure. The general structural formula is as follows: Wherein, A is an aromatic group, and X has a value of 50-99.
2. A highly alkali-resistant in-situ cross-linked anion exchange polymer according to claim 1, characterized in that: The aryl group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene.
3. A method for preparing a highly alkali-resistant in-situ cross-linked anion exchange polymer, characterized in that: The specific steps are as follows: 100 parts of an aromatic compound and 100 parts of quinuclidinone hydrochloride or 3-quinuclidinone are mixed in a solvent, reacted with Lewis acid at 0°C, impurities are removed, and dried to obtain an intermediate polymer; 100 parts of the intermediate polymer, 1-50 parts of p-chloromethylstyrene and 100-1000 parts of methyl iodide are mixed, reacted under alkaline conditions, filtered, washed and dried to obtain an anion exchange polymer.
4. The method for preparing a highly alkali-resistant in-situ cross-linked anion exchange polymer according to claim 3, characterized in that: The general structural formula of the anion exchange polymer is as follows: Wherein, A is an aromatic group, and X has a value of 50-99.
5. The method for preparing a highly alkali-resistant in-situ cross-linked anion exchange polymer according to claim 4, characterized in that: The aryl group is one or more of biphenyl, p-terphenyl, m-terphenyl, diphenylethane, and 9,9-dimethylfluorene.
6. A highly alkali-resistant in-situ cross-linked anion exchange membrane, characterized in that: The invention adopts a highly alkali-resistant in-situ cross-linked anion exchange polymer, and the general structural formula of the highly alkali-resistant in-situ cross-linked anion exchange polymer is as follows: Wherein, A is an aromatic group, and X has a value of 50-99.
7. A highly alkali-resistant in-situ cross-linked anion exchange membrane according to claim 6, characterized in that: The highly alkali-resistant in-situ cross-linked anion exchange polymer is prepared by the following method: 100 parts of an aromatic compound and 100 parts of quinuclidinone hydrochloride or 3-quinuclidinone are mixed in a solvent, reacted with Lewis acid at 0°C, impurities are removed, and dried to obtain an intermediate polymer; 100 parts of the intermediate polymer, 1-50 parts of p-chloromethylstyrene and 100-1000 parts of methyl iodide are mixed, reacted under alkaline conditions, filtered, washed and dried to obtain an anion exchange polymer.
8. The method for preparing a highly alkali-resistant in-situ cross-linked anion exchange membrane according to claim 6 or 7, characterized in that: A highly alkali-resistant in-situ cross-linked anion exchange polymer solution with a mass fraction of 1% to 50% is poured into the template and dried to obtain an anion exchange membrane.
9. The method for preparing a highly alkali-resistant in-situ cross-linked anion exchange membrane according to claim 8, characterized in that: The drying is carried out at 50° C. to 120° C. for 30 min to 12 h.
10. A water electrolysis reactor, characterized in that: It comprises the highly alkali-resistant in-situ cross-linked anion exchange membrane as described in claim 6.